Tourism marketing and management handbook - Witt, Stephen F.; Moutinho, Luiz (Prentice Hall, 1994)
This handbook provides a detailed guide to marketing and management in tourism in the 1990s. This second edition features 100 contributions from international authorities on the subject; new chapters reflecting the issues of increasing importance in tourism; greater emphasis on management and internationally applicable topics; and major revisions of all existing chapters. The contents have been reorganized by subject area for convenience. Designed to provide a user-friendly reference, the topics covered include cost-benefit analysis, hotel marketing, international tourism trends, financial analysis and planning, quality management and pricing and promotional strategy. This edition shows the application of marketing and mangement techniques within the tourism industry, and is appropriate for use in tourism businesses of any size.